Biomass Estimation of Two Eucalyptus Species by Regression Method - Negi, J. D. S.; Sharma, D. C. (Indian Forester, 1987)
A set of regression lines has been obtained from the biomass data of Eucalyptus species growing in Tamil Nadu and using these equations, it is possible to predict the biomass from the measurement of diameter and height, without felling the trees.